Three for Ajay: Learning at “The Other Side of Nowhere” - Watkins, Paul (Critical Studies in Improvisation / Études critiques en improvisation, 2025)
Paul Watkins reflects on his relationship with Ajay Heble, with particular focus on his work with the Improvisation, Community, and Social Practice project (ICASP).